A particularidade histórica da pesquisa no serviço social - Bourguinon, Jussara Ayres (2005)
This thesis aims at reflecting on the historical particularity of research into Social Work, as well as on the resultant challenges of such particularity presented to Social Work in the contemporary context. Three essential pillars oriented the investigation process. They are: the particularity of research for Social Work; the centrality occupied by persons that participate of Social Work researches; the return and the social reach of researches developed for Social Work. The investigation process was developed supported in methodological resources that made possible the construction of theoretical referential, the approach to the persons that participated of the research through interviews and electronic declarations, and the development of systematization and critical analysis of the set of empirical and theoretical material, that in its synthesis constitutes the defended thesis. The participants of the research were persons considered representative of the Social Worker professional category because the density of experiences they have on research, making possible reflections that evidence latent worries and that are pertinent to the production of knowledge in Social Work. The thesis presentation was organized in two moments. The first moment deals with the production of knowledge as human work expression. In this purpose, it contextualizes the advancements reached for Social Work mainly during the 80 s and 90 s and presents the comprehension of the knowledge production process as one of the human labor expressions, in a historical critical perspective. The second moment deals with the elements that constitute the particularity of research for the participant persons, considering the orienting pillars of the thesis. Such moment express, in its totality, the syntheses constructed in order to articulate the theoretical fundamentals to the collected declarations, searching for comprehending how the particularity of the research takes expression and materiality in Social Work. We reaffirm, through the investigation process, the proposition that the research is constitutive and constituent of the Social Work professional practice, being determined for its interventive nature and for its historical insertion in sociotechnical labor sharing